Abstracts of the 4th International Electronic Conference on Cancers (IECC2024): Insights into Cancer Metastasis, Biomarkers, Microenvironment, Immunotherapy, Pathophysiology, and Prevention - Angeliki Magklara; Shinji Kawabata; Alfredo Conti; Vasso Apostolopoulos (Proceedings)
The 4th International Electronic Conference on Cancers (IECC 2024), organized by the MDPI journal Cancers, was an online event held on 6–8 March 2024 [...]